Characterization of Raw Starch Digesting and Adsorbing Extra Cellular Isoamylase from Rhizopus oryzae - Rina Rani Ray, Barnita Ghosh and (Recent Research in Science and Technology, 2010)
The partially purified extra cellular isoamylase produced by Rhizopus oryzae PR7 MTCC 9642, was characterized for various parameters. It showed highest affinity towards oyster glycogen followed by starch and amylopectin. The temperature and pH optima were found to be at 55° C and 5 respectively. The enzyme was found to be stable at 55°C for 10 minutes and at a broad pH range of 4-8. Increase in stability in presence of thiol additives and deactivation in presence of thiol inhibitors indicated the existence of thiol groups at the active site of the enzyme. The enzyme could digest raw native starches collected from various wastes of which rice extract and bread dust showed the highest extent of saccharification. Glucose and maltose were the major end products of starch bioconversion by the isoamylase. The isoamylase was found to be adsorbed onto various raw starch molecules, the rate of adsorption and desorption was best onto corn starch molecules.